Comparing early life nutritional sources and human milk feeding practices: personalized and dynamic nutrition supports infant gut microbiome development and immune system maturation. (31st December 2023) - Ames, Spencer R.; Lotoski, Larisa C.; Azad, Meghan B.
ABSTRACT: Exclusive breastfeeding is recommended for the first six months of life, but many infants receive pumped milk, formula, donor human milk, or other nutritional sources during this critical period. Substantive evidence shows early nutrition influences development of the microbiome and immune system, affecting lifelong health. However, the underlying mechanisms are unclear and the nuances of human milk feeding are rarely considered. This review synthesizes evidence from human studies and model systems to discuss the impact of different nutritional sources on co-development of the gut microbiome, antigen tolerance, and immunity. We highlight two key mechanisms: epigenetics and the so-called "weaning reaction". Collectively, this evidence highlights i) the fundamental role of parents' own milk, fed directly at the breast, as a dynamic and personalized nutrition source that drives developmental programming, and ii) the deficiencies of alternative nutritional sources and priority research areas for improving these alternatives when direct breastfeeding is not possible. Plain Language Summary: Before they begin eating solid foods, infants may be fed a variety of nutritional sources such as breast milk ("parent's own milk", fed directly at the breast or pumped and fed from a bottle), commercial infant formula, or sterilized "donor human milk" from a certified milk bank. Early nutrition affects the infant's gut microbiome (bacteria living in the intestinal tract), development of their immune system, and their health throughout life. However, it is unclear how different forms of early nutrition affect these important processes. Parent's own milk contains compounds that support gut microbes and stimulate development of the infant immune system, changing over time to meet infant needs. For many of these compounds, donor human milk contains a lesser amount, and formula contains even less – or none at all. Some compounds are also affected by pumping and storing parents' own milk. This review highlights how differences among these nutritional sources influence gene expression and gut development to shape the infant microbiome and immune system. Current evidence shows that parent's own milk, fed at the breast, offers unique benefits that are not replicated by other forms of early nutrition. This review also outlines how early life nutrition research can help us understand human development and develop new ways to provide the best possible start to life for all infants.